JDM AT THE CORE OF ACCOUNTING - G, Dr. Shivaprasad; Chavare, Kavita (The journal of contemporary issues in business and government, 2022)
The purpose of this research is to look into the qualifying effect of capital structure components on the accounting-related quality of judgement and decision-making (JDM). The framework is used to study the variation in JDM quality by taking the practical significance of the study in an applied field. The study found evidence that different capital structures having both secured and unsecured loans have an impact on accounting-related JDM quality by studying the transformation in the net worth as a result of the volatility of earning and the economic consequences of 3 C dimensions on earnings are analyzed to measure the JDM quality. This study documents a variation in the quality of the informativeness of the treated firm’s financial reports. As a research method, we undertook the one-way Annova The study concluded that the Hybrid and high debt capital structures with both secured and unsecured loans influence the adoption of aggressive accounting practices and, as a result, a reduction in the informativeness of firms’financial reporting.